AN ASSESSMENT OF THE STATUS OF HIV COUNSELLING AND TESTING FACILITY IN GOVERNMENT HOSPITALS OF DISTRICT JHANSI UTTAR PRADESH - Singh, Atul Kumar; Srivastav, Shalini; Kariwal, Peeyush; Mathur, B P (Indian Journal of Community Health, 2010)
Background: Counseling is the face to face communication by which counselor can help the person” client to make decisions and act on them, Effective Counseling and Testing programs can help patients identify and limit- behaviors that increase the risk of’ HIV infection or transmission. Objective: ToAssess the status of HlV Counseling and Testing facilities in Government Hospitals of District Jhansi. Study design: Cross-sectional study. Settings: Four Government Hospitals namely Mèdical College, District Hospital, Railway Hospital and Military Hospital of district Jhansi. Study Period: Two months (l5th August to 15’ October 2008.) StatisticalAnalysis: Percentages Results: In most (87.5%) of the sessions of all the centers only signature of the patients was taken instead of filling the full consent form whereas rapport with the patients by the counselor was maintained only in 37.5% sessions. In 80% of the sessions the patients were not been told about ‘window period” by the counselors. In 75% of the sessions counselors were not fully attentive towards patient’s concerns. Only in 5% sessions patients were correctly informed about HI V/AIDS. In all the centers, there was no provision for group- session and usually the test results of HlV infection (positive or negative) was not provided on the very same day, due to heavy patient load.